Wife Elegy between Two Visions: New Horizons for the Contemporary Prose Poem (Journal of the College of Basic Education, 2025)
The vision of the prose poem draws a distinct borderline between elegy and its purpose, concept and meaning. This vision marks the first step toward transformation, in other words, an act of poetic re-creation. It raises critical questions: Can elegy be liberated from its conventional purpose? Must it be uncovered of its traditional function? Where does the poetics of the text reside? And will the function of the elegy become, paradoxically, an anti-elegy? Contemporary elegy, especially in prose poetry, has clearly moved beyond mere lamentation or weeping. It has evolved into a semiotic and narrative form, an “open message” that does not seek a response as much as it reconstructs being in the shadow of loss. This new conception of elegy does not solely belong to the past; rather, it is revived in the text as a daily ritual that restores life to the deceased through language, not by summoning the dead, but by symbolically representing their presence.